Anti-discoloration solid ceramic chip, solid ceramic perfumed chip and preparation method of solid ceramic perfumed chip
By using a mixture of absorbent and nano-scale synthetic calcium in solid aromatherapy tablets, the problem of discoloration after aromatherapy tablets is solved, and the color stability and aesthetics of aromatherapy tablets are improved.
Patent Information
- Application Number
- CN202411799340.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
Existing solid adsorbent aromatherapy tablets are prone to discoloration after absorbing fragrance, which affects the beauty of the product. The traditional solution has a long cycle and is difficult to maintain the original shape of the fragrance.
A mixture of decolorizing agents such as titanium dioxide, titanium dioxide, silica, zinc oxide, mica powder, talc powder and nano-scale synthetic calcium is prepared through ultrasonic stirring and molding process.
It effectively avoids discoloration caused by fragrance ingredients and environmental factors, maintains the color stability and aesthetics of fragrance sheets, and enhances the competitiveness of the product.
Smart Images

Figure CN119613136A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of indoor aromatherapy and automobile fragrance system, and in particular to an anti-discoloration solid porcelain sheet, a solid ceramic fragrance sheet and a preparation method thereof. Background Art
[0002] Air fresheners currently on the market are mainly divided into liquid, solid paste aromatherapy and solid adsorption types according to their physical state. The amount of fragrance added is related to the properties of the specific carrier material. Air fresheners for different purposes are produced according to different volatility properties.
[0003] Solid air freshener aromatherapy generally adds 50-60% fragrance according to different carrier applications. For solid adsorption aromatherapy, a more troubling problem is that the aromatherapy tablets have serious discoloration after absorbing fragrance; there are three main reasons: first, the material of the aromatherapy carrier is affected. The commonly used carriers are mainly derived from natural minerals, such as calcium silicate / calcium carbonate, etc. These natural minerals contain a certain amount of iron ions. These iron ions will produce certain group substitution reactions with the complex fragrance raw materials in the fragrance after the fragrance tablets absorb fragrance, resulting in discoloration. The second is that some fragrance raw materials in the fragrance will also change color under a certain humidity and oxygen environment, such as ethyl vanillin, ethyl maltol, indole, eugenol, etc.; the third is the influence of the aromatherapy tablet pressing process. Common solid adsorption aromatherapy tablets are made of ultra-fine mineral powder pressed by a special process. After absorbing fragrance, the sheet structure has a certain permeability, and the color change of the fragrance tablet will be obvious.
[0004] The traditional solution to the discoloration of aromatherapy tablets is mainly to modify the essence. Not only is the cycle long (usually 1-2 months), but it is also very easy to modify the selected fragrance to be too different from the original smell, which fails to achieve the desired effect of the project. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art, the present invention provides a discoloration-resistant solid ceramic scented sheet, aiming to solve the problem that the ceramic scented sheet in the prior art solution is easy to discolor and affects the appearance of the product.
[0006] The purpose of the present invention is achieved through the following technical solutions
[0007] In a first aspect, the present invention provides an anti-discoloration solid ceramic sheet, which is prepared from the following raw materials in parts by weight: 75-80 parts of powder, 7-10 parts of plant fiber, 1-2 parts of titanium dioxide, 1-2 parts of titanium dioxide, 1-2 parts of silicon dioxide, 1-2 parts of zinc oxide, 1-2 parts of mica powder, 1-2 parts of talc, 3-4 parts of pressed gelling agent, 1-2 parts of release agent, 1-2 parts of deionized water, and 1-2 parts of dispersant.
[0008] Furthermore, the powder is one or more combinations of calcium silicate, light calcium carbonate, calcium oxide, and silicon dioxide, and the particle size of the powder is 10 to 80 μm.
[0009] Furthermore, the plant fiber is one or more combinations of cotton, flax, ramie, jute and bamboo fiber.
[0010] Furthermore, the particle size of the titanium dioxide is 0.2-0.3 μm, the whiteness value is 95-96, and the dispersibility is 5.5-6. 。
[0011] Furthermore, the zinc oxide has a particle size of 1-10 μm and a purity of 99.7%. A high purity means fewer impurities, which can reduce the impact of other products on the main product, thereby improving the purity and stability of the product.
[0012] Furthermore, the mica powder has a particle size of 10 μm.
[0013] Furthermore, the compression gel is one or more combinations of polyvinyl alcohol, sodium alginate, gelatin, and polyacrylic acid.
[0014] Furthermore, the release agent is one or more combinations of polyphenylmethylsiloxane, palmityl palmitate, and stearic acid.
[0015] Furthermore, the dispersant is one or more combinations of water, polyethylene glycol, and glycerol.
[0016] In a second aspect, the present invention provides a method for preparing a discoloration-resistant solid ceramic sheet, the method being used to prepare the discoloration-resistant solid ceramic sheet as described in the first aspect, the method comprising the following steps:
[0017] S1. Take 1 / 2 of the dispersant and mix it with titanium dioxide, titanium dioxide, silicon dioxide, zinc oxide, mica powder and talcum powder to form a suspension to improve the dispersibility of the decolorizer;
[0018] S2. Add the suspension and the remaining 1 / 2 of the dispersant to the powder, and stir evenly using an ultrasonic stirrer to break up the agglomerates of the decolorizer and ensure that it is evenly dispersed without particles, thereby improving the whiteness and hiding power of the product;
[0019] S3, fully mixing the powder obtained after uniform mixing in step S2 with the plant fiber and the pressed gelling agent to obtain a mixed powder;
[0020] S4, adding deionized water to the mixed powder obtained in step S3, stirring evenly to prepare a premix; adding a release agent to the premix to prepare a mixture;
[0021] S5. Take the mixed material obtained in step S4 and prepare an anti-discoloration solid ceramic sheet by molding.
[0022] Furthermore, in step S2, the stirring speed is 1500 rpm and the time is 3-5 minutes.
[0023] Furthermore, in step S5, the mixed material obtained in step S4 is placed in a mold, and a discoloration-resistant solid ceramic sheet is prepared by compression molding.
[0024] Furthermore, in step S5, the filling height of the mold is 43 mm.
[0025] Furthermore, in step S5, during compression molding, the downward pressure of the upper mold in the mold is 120 Kgf, and the downward time is 4 s; the upward pressure of the lower mold is 80 Kgf, and the upward time is 1.5 s.
[0026] In a third aspect, the present invention provides a solid ceramic scented sheet, which is prepared by adsorbing essence using the anti-discoloration solid ceramic sheet as described in the first aspect.
[0027] The present invention develops a new type of anti-discoloration solid ceramic fragrance sheet with titanium dioxide, titanium dioxide, silicon dioxide, zinc oxide, mica powder and talcum powder as decolorants. At present, the carrier raw materials used in solid adsorption aromatherapy are generally nano-scale synthetic calcium. The present invention uses the whitening and light-shielding characteristics of the decolorant to block the color. Its high refractive index and excellent light scattering properties, combined with the mixed production of nano-scale synthetic calcium mixtures, can increase the decolorization power of the solid fragrance body. Second, the chemical stability of the decolorant enables it to resist the influence of ultraviolet rays, temperature changes and climatic conditions, and maintain color stability and durability. In addition, the particle size of the decolorant is usually very small, reaching the nanometer level, which can provide a uniform coating effect, further enhance its covering performance, and evenly mix with the solid powder to absorb fragrance. The anti-discoloration technology with the addition of the decolorant can bring more fragrance possibilities to human life, no longer fear the choice of fragrances that are easy to change color, enhance the expressiveness of the product, bring consumers a better user experience, and make solid aromatherapy more competitive in aromatherapy products.
[0028] Compared with the existing technical solutions, the solid aromatherapy porcelain sheet of the present invention has the following advantages:
[0029] The present invention makes ceramic scented sheets by adding a decolorizing agent into a traditional aromatherapy formula, which can effectively avoid the discoloration of the scented sheets caused by raw material components such as ethyl vanillin, ethyl maltol, indole, eugenol, and aroma deodorizing agents. Improving the discoloration of solid scented sheets can make the aroma present more possibilities and make the aroma expression unlimited.
[0030] Decolorizers can also effectively improve the appearance and achieve beautiful aromatherapy shapes. For other shapes of ceramic products, such as petal-shaped scented ceramic products, the edges of the petals often turn yellow while the flower body is relatively clean. This is because the petals evaporate slowly and accumulate more residual color-changing aroma raw materials. When the aromatherapy tablets contain decolorizers, the petals will not turn yellow.
[0031] Decolorants can also improve discoloration caused by storage environment. Solid aromatherapy is safe, easy to store and handle. Compared with liquid aromatherapy, solid aromatherapy is not easy to splash or leak, which is suitable for users who want to avoid accidents. Therefore, solid aromatherapy is also a very popular product among many aromatherapy products, but its disadvantages are also very obvious. The in-car environment is relatively complex, and high temperature and other conditions can easily cause discoloration. The anti-discoloration technology with the addition of decolorants can make solid aromatherapy more competitive among many products. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the color change test of solid ceramic scented sheet A.
[0033] Figure 2 Schematic diagram of the color change test of solid ceramic scented sheet B.
[0034] Figure 3 Schematic diagram of the color change test of solid ceramic scented sheet C.
[0035] Figure 4 Schematic diagram of the color change test of solid ceramic scented sheet D.
[0036] Figure 5 Schematic diagram of the color change test of solid ceramic scented sheet E.
[0037] Figure 6 Schematic diagram of the color change test of solid ceramic scented sheet F. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments are described clearly and completely below. Obviously, the embodiments described below are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0040] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.
[0041] The raw materials involved in the present invention can be directly purchased from the market. For process parameters not specifically noted, conventional techniques can be used.
[0042] The raw materials in the examples and comparative examples of the present invention are introduced as follows:
[0043] Calcium silicate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 1344-95-2; particle size 10-80 μm;
[0044] Flax was purchased from Jingde County Jinwei Flax Industry Co., Ltd.;
[0045] Titanium dioxide was purchased from Shanghai Shunyi Chemical Co., Ltd.; the particle size was 0.2-0.3 μm, the whiteness was measured by MS-350 whiteness tester, the whiteness value was 95-96, and the dispersibility was expressed by Hegman number, the dispersibility was 5.5-6;
[0046] Titanium dioxide was purchased from Shanghai Shunyi Chemical Co., Ltd.;
[0047] Silicon dioxide was purchased from Weifang Sanjia Chemical Co., Ltd.;
[0048] Zinc oxide was purchased from Weifang Aolong Zinc Industry Co., Ltd.; purity 99.7%;
[0049] Mica powder was purchased from Zhongke Mineral Powder Co., Ltd., Lingshou County, Hebei Province; particle size was 10 μm;
[0050] Talc was purchased from Dongguan Sanfeng Chemical Co., Ltd.;
[0051] Polyvinyl alcohol was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 9002-89-5;
[0052] Palmitate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a CAS number of 540-10-3.
[0053] Example 1
[0054] The present embodiment provides an anti-discoloration solid ceramic sheet, which is prepared from the following raw materials in parts by weight: 78 parts of calcium silicate, 10 parts of flax, 1 part of titanium dioxide, 1 part of titanium dioxide, 1 part of silicon dioxide, 1 part of zinc oxide, 1 part of mica powder, 1 part of talc, 3 parts of polyvinyl alcohol, 1 part of palmityl palmitate, 1 part of deionized water, and 1 part of polyethylene glycol.
[0055] Made by the following preparation method:
[0056] S1, take 0.5 parts by weight of polyethylene glycol and mix with 1 part of titanium dioxide, 1 part of titanium dioxide, 1 part of silicon dioxide, 1 part of zinc oxide, 1 part of mica powder and 1 part of talc to form a suspension;
[0057] S2, adding the suspension and the remaining 0.5 parts by weight of polyethylene glycol to 78 parts of calcium silicate, and using an ultrasonic stirrer to stir at a speed of 1500 rpm for 3-5 minutes;
[0058] S3, fully mixing the powder obtained after uniform mixing in step S2 with 10 parts of flax and 3 parts of polyvinyl alcohol to obtain a mixed powder;
[0059] S4, adding 1 part of deionized water to the mixed powder obtained in step S3, stirring evenly to prepare a premix; adding 1 part of polyethylene glycol to the premix to prepare a mixed material;
[0060] S5. Place the mixture obtained in step S4 in a mold with a mold filling height of 43 mm. During compression molding, the downward pressure of the upper mold is 120 kgf and the downward time is 4 s; the upward pressure of the lower mold is 80 kgf and the upward time is 1.5 s to prepare a discoloration-resistant solid ceramic sheet.
[0061] Example 2
[0062] The present embodiment provides an anti-discoloration solid ceramic sheet, which is prepared from the following raw materials in parts by weight: 75 parts of calcium silicate, 7 parts of flax, 2 parts of titanium dioxide, 2 parts of titanium dioxide, 1 part of silicon dioxide, 1 part of zinc oxide, 2 parts of mica powder, 2 parts of talc, 3 parts of polyvinyl alcohol, 1 part of palmityl palmitate, 2 parts of deionized water, and 2 parts of polyethylene glycol.
[0063] Made by the following preparation method:
[0064] S1, take 1 part by weight of polyethylene glycol and mix it with 2 parts of titanium dioxide, 2 parts of titanium dioxide, 1 part of silicon dioxide, 1 part of zinc oxide, 2 parts of mica powder and 2 parts of talc to form a suspension;
[0065] S2, adding the suspension and the remaining 1 part by weight of polyethylene glycol to 75 parts of calcium silicate, and using an ultrasonic stirrer to stir at a speed of 1500 rpm for 3-5 minutes;
[0066] S3, fully mixing the powder obtained after uniform mixing in step S2 with 7 parts of flax and 3 parts of polyvinyl alcohol to obtain a mixed powder;
[0067] S4, adding 2 parts of deionized water to the mixed powder obtained in step S3, stirring evenly to prepare a premix; adding 2 parts of polyethylene glycol to the premix to prepare a mixed material;
[0068] S5. Place the mixture obtained in step S4 in a mold with a mold filling height of 43 mm. During compression molding, the downward pressure of the upper mold is 120 kgf and the downward time is 4 s; the upward pressure of the lower mold is 80 kgf and the upward time is 1.5 s to prepare a discoloration-resistant solid ceramic sheet.
[0069] Example 3
[0070] The present embodiment provides an anti-discoloration solid ceramic sheet, which is prepared from the following raw materials in parts by weight: 76 parts of calcium silicate, 8 parts of flax, 2 parts of titanium dioxide, 2 parts of titanium dioxide, 2 parts of silicon dioxide, 1 part of zinc oxide, 2 parts of mica powder, 1 part of talc, 3 parts of polyvinyl alcohol, 1 part of palmityl palmitate, 1 part of deionized water, and 1 part of polyethylene glycol.
[0071] Made by the following preparation method:
[0072] S1, take 0.5 parts by weight of polyethylene glycol and mix with 2 parts of titanium dioxide, 2 parts of titanium dioxide, 2 parts of silicon dioxide, 1 part of zinc oxide, 2 parts of mica powder, and 1 part of talc to form a suspension;
[0073] S2, adding the suspension and the remaining 0.5 parts by weight of polyethylene glycol to 76 parts of calcium silicate, and using an ultrasonic stirrer to stir at a speed of 1500 rpm for 3-5 minutes;
[0074] S3, fully mixing the powder obtained after uniform mixing in step S2 with 8 parts of flax and 3 parts of polyvinyl alcohol to obtain a mixed powder;
[0075] S4, adding 1 part of deionized water to the mixed powder obtained in step S3, stirring evenly to prepare a premix; adding 1 part of polyethylene glycol to the premix to prepare a mixed material;
[0076] S5. Place the mixture obtained in step S4 in a mold with a mold filling height of 43 mm. During compression molding, the downward pressure of the upper mold is 120 kgf and the downward time is 4 s; the upward pressure of the lower mold is 80 kgf and the upward time is 1.5 s to prepare a discoloration-resistant solid ceramic sheet.
[0077] Comparative Example 1
[0078] This comparative example provides a solid ceramic sheet, which is prepared from the following raw materials in parts by weight: 80 parts of calcium silicate, 10 parts of flax, 4 parts of polyvinyl alcohol, 2 parts of palmityl palmitate, 2 parts of deionized water, and 2 parts of polyethylene glycol.
[0079] Made by the following preparation method:
[0080] S1. Fully mix 80 parts of calcium silicate, 10 parts of flax and 4 parts of polyvinyl alcohol to prepare a powder;
[0081] S2, adding 2 parts of deionized water to the powder, stirring evenly to prepare a premix;
[0082] S3, adding 2 parts of palmityl palmitate to the premix to prepare a mixture;
[0083] S4. Place the mixed material in a mold with a mold filling height of 43 mm. During compression molding, the downward pressure of the upper mold is 120 kgf and the downward time is 4 s; the upward pressure of the lower mold is 80 kgf and the upward time is 1.5 s to prepare a ceramic sheet.
[0084] 1. Color change test at 70 degrees Celsius
[0085] The solid ceramic piece prepared in Comparative Example 1 was immersed in the fragrance liquid to fully absorb the fragrance for 2 hours, then the ceramic piece was taken out, and the fragrance liquid remaining on the surface was wiped off to prepare a solid ceramic fragrance piece A.
[0086] The anti-discoloration solid ceramic sheet prepared in Example 1 was immersed in the fragrance liquid to fully absorb the fragrance for 2 hours, then the ceramic sheet was taken out and the fragrance liquid remaining on the surface was wiped off to prepare a solid ceramic fragrance sheet B.
[0087] Take one ceramic scent piece A and one ceramic scent piece B of the same weight, observe them at 70 degrees Celsius for one month, and observe the color change at room temperature every 10 days. The final test results are as follows: Figure 1 , Figure 2 shown.
[0088] 2. Color change test caused by fragrance
[0089] The solid ceramic piece prepared in Comparative Example 1 was immersed in vanillin essence to fully absorb the fragrance for 2 hours to prepare a solid ceramic scented piece C.
[0090] The solid ceramic piece prepared in Example 2 was immersed in vanillin essence to fully absorb the fragrance for 2 hours to prepare a solid ceramic scented piece D.
[0091] Take the same weight of solid ceramic scented tablets C and D, observe them under sufficient light for one month, and observe the color change at room temperature every 10 days. The final test results are as follows: Figure 3 , Figure 4 shown.
[0092] 3. Color change test caused by iron ions
[0093] The anti-discoloration solid ceramic sheet prepared in Comparative Example 1 was immersed in eugenol essence to fully absorb the fragrance for 2 hours, so as to prepare a solid ceramic fragrance sheet E.
[0094] The solid ceramic piece prepared in Example 3 was immersed in eugenol essence to fully absorb the fragrance for 2 hours to prepare a solid ceramic fragrance piece F.
[0095] Take solid ceramic scented tablets E and solid ceramic scented tablets F of the same weight and observe them at room temperature for one month. Every 10 days, observe the color change at room temperature. The final test results are as follows: Figure 5 , Figure 6 shown.
[0096] From the comparison of the above test results, it can be seen that the anti-discoloration solid ceramic scent sheet of the present invention can avoid the discoloration problem of aromatherapy powder caused by high temperature, flavors, iron ions, etc. Compared with ordinary ceramic scent sheets, the anti-discoloration solid ceramic scent sheet of the present invention has better color stability and aesthetics, and is therefore more competitive in the market.
[0097] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A discoloration-resistant solid ceramic sheet, characterized in that: The anti-discoloration solid ceramic sheet is prepared from the following raw materials in parts by weight: 75-80 parts of powder, 7-10 parts of plant fiber, 1-2 parts of titanium dioxide, 1-2 parts of titanium dioxide, 1-2 parts of silicon dioxide, 1-2 parts of zinc oxide, 1-2 parts of mica powder, 1-2 parts of talc, 3-4 parts of pressing gelling agent, 1-2 parts of release agent, 1-2 parts of deionized water and 1-2 parts of dispersant.
2. The anti-discoloration solid ceramic sheet according to claim 1, characterized in that: The powder is one or more combinations of calcium silicate, light calcium carbonate, calcium oxide and silicon dioxide, and the particle size of the powder is 10 to 80 μm.
3. The anti-discoloration solid ceramic sheet according to claim 1, characterized in that: The plant fiber is one or more combinations of cotton, flax, ramie, jute and bamboo fiber.
4. The anti-discoloration solid ceramic sheet according to claim 1, characterized in that: The particle size of the titanium dioxide is 0.2-0.3 μm, the whiteness value is 95-96, and the dispersibility is 5.5-6. 。 5. The anti-discoloration solid ceramic sheet according to claim 1, characterized in that: The laminating gel is one or more combinations of polyvinyl alcohol, sodium alginate, gelatin and polyacrylic acid; the demoulding agent is one or more combinations of polyphenylmethylsiloxane, palmityl palmitate and stearic acid.
6. The anti-discoloration solid ceramic sheet according to claim 1, characterized in that: The dispersant is one or more combinations of water, polyethylene glycol and glycerol.
7. A method for preparing a discoloration-resistant solid ceramic sheet, characterized in that: The preparation method is used to prepare the anti-discoloration solid ceramic sheet according to any one of claims 1 to 6, and the preparation method comprises the following steps: S1, take 1 / 2 of the dispersant and mix it with titanium dioxide, titanium dioxide, silicon dioxide, zinc oxide, mica powder and talc to form a suspension; S2, adding the suspension and the remaining 1 / 2 of the dispersant to the powder, stirring evenly with a stirrer to obtain a powder; S3, fully mixing the powder obtained after uniform mixing in step S2 with the plant fiber and the pressed gelling agent to obtain a mixed powder; S4, adding deionized water to the mixed powder obtained in step S3, stirring evenly to prepare a premix; adding a release agent to the premix to prepare a mixture; S5. Take the mixed material obtained in step S4 and prepare an anti-discoloration solid ceramic sheet by molding.
8. The preparation method according to claim 7, characterized in that: In step S2, the stirring speed is 1500 rpm and the time is 3-5 minutes.
9. The preparation method according to claim 7, characterized in that: In step S5, the mixed material obtained in step S4 is placed in a mold, and a discoloration-resistant solid ceramic sheet is prepared by compression molding.
10. A solid ceramic scented sheet, characterized in that: The anti-discoloration solid ceramic sheet according to any one of claims 1 to 7 is used to adsorb flavor to prepare the product.